Occupational Segregation and Equal Pay for Work or Equal Value - Robb, Roberta (Relations industrielles / Industrial Relations, 1984)
The recent federal «Equal Pay for Work of Equal Value» legislation challenges the usual supply-demand mechanism of wage determination. This paper analyzes the legislation within the context of economic models of occupational segregation and occupational wage differentials. The aim is to assess whether or not the legislation is likely to produce any significant negative side effects (such as unemployment) for women in the labour market.